Enterprise Architecture Model of the New Student Admission System at Stella Maris University Sumba - Ledi, Dian Fransiska; Dapadeda, Ardiyanto (Journal of Applied Informatics and Computing, 2024)
This research aims to design an Enterprise Architecture (EA) model for the new student admission system at Stella Maris Sumba University. The background of this research is the need to improve efficiency, transparency, and integration in the new student admission process, which currently still faces various administrative and technical challenges. The research method used is qualitative which includes literature studies and in-depth interviews with relevant parties. The data obtained was analyzed to identify needs and design the right EA model. The purpose of this research is to create a system capable of automating the admission workflow, ensuring data security, and providing real-time access for application status tracking. The results showed that the proposed Enterprise Architecture model can improve operational efficiency, user satisfaction, and support the strategic decisions of Stella Maris Sumba University based on accurate and integrated data.